Exercise enhances motor skill learning by neurotransmitter switching in the adult midbrain - Hui-quan Li (Nature Portfolio, 2020)
Exercise promotes motor skill learning via unclear mechanisms. Here, the authors show that running wheel training results in neurotransmitter switching in caudal pedunculopontine nucleus neurons of mice. These neurons project to several brain regions, regulating the acquisition of motor skills.